Field Efficacy of Several Selected Insecticides Against the Diamondback moth, Plutella xylostella (L)1, on Cabbage, Brassica oleracea var. capitata (L), in the Lowland of Malaysia - Mohamad, Rosli; Ibrahim, Yusof; Chong, Wei Cheong (1979)
l!.1ficacy of several selected insecticides available in the market were tested against the Diamondback moth, Plutella xylostella (L), on cabbage, Brassica oleracea val'. capitata (L), in the lowland (University of Agriculture Malaysia farm). Ir~ general, the results showed that acephate, methamidophos, and bendiocarb all at 0.1% a.i., Bacillus thuringiensis at 1g./I., diflubenzuron at 0.007% a.i., each in 450 I. of water/ha. caused significant reduction (P~ 0.05) in larval population. These insecticides also provided equal protection against larval damage on young hearting leaves of cabbage. Consistently, the control plots gave significantly lower yield (P ~ 0.05) of marketable heads as compared to the insecticide treated plots.